Drug-drug interactions between direct oral anticoagulants and anticonvulsants and clinical outcomes: A systematic review - Candeloro, Matteo; Carlin, Stephanie; Shapiro, Michelle J.; Douketis, James D. (Research and practice in thrombosis and haemostasis, 2023)
Direct oral anticoagulants (DOACs) are widely used in patients with atrial fibrillation and venous thromboembolism. However, DOACs have important potential drug-drug interactions (DDIs) with several classes of drugs. In particular, antiepileptic (AE) drugs may induce cytochrome P450 3A4 or P-glycoprotein. Co-administration of DOACs and AE drugs may result in lower DOAC drug levels and reduced DOAC efficacy. However, the clinical significance of such DDIs is uncertain. The aim of this systematic review was to generate an updated review of these DDIs and their clinical relevance, given the rapidly evolving knowledge relating to DOAC and AE DDIs. We searched the MEDLINE and Embase databases for studies reporting clinical adverse outcomes (thrombotic events, bleeding events, and all-cause mortality) in patients concomitantly taking DOACs and AE drugs. We retrieved 874 studies of which 15 were deemed eligible for this review, including 4 congress abstracts, 3 case reports, 2 letters to the editor, 5 retrospective cohorts, and 1 prospective cohort study. No randomized clinical trials were found. Most of the included studies reported thrombotic events, 3 studies reported major bleeding, and one study reported all-cause mortality associated with DOAC and AE drug administration. Substantial differences in the study designs did not allow for a meta-analysis to be performed. The current literature assessing these adverse clinical outcomes from DOAC and AE drug co-administration is limited. Although the available data point to a possible increased risk of thrombotic events, they are insufficient to draw definitive conclusions. Well-designed clinical studies are of utmost importance. •Direct oral anticoagulants (DOACs) and antiepileptic drugs are often co-administered.•Co-administration of DOACs and antiepileptic drugs may result in lower DOAC efficacy.•These drug-drug interactions (DDIs) may result in adverse clinical events such as thrombosis.•Current data are insufficient to draw conclusions about these DDIs and adverse clinical events.